2005
DOI: 10.1007/s00438-005-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mRNA profiling in glucose starved Bacillus subtilis cells

Abstract: In this study global changes in gene expression were monitored in Bacillus subtilis cells entering stationary growth phase owing to starvation for glucose. Gene expression was analysed in growing and starving cells at different time points by full-genome mRNA profiling using DNA macroarrays. During the transition to stationary phase we observed extensive reprogramming of gene expression, with approximately 1,000 genes being strongly repressed and approximately 900 strongly up-regulated in a time-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 49 publications
0
56
1
1
Order By: Relevance
“…An obvious explanation for the high degree of protein breakdown demonstrated by our wild-type pulse-chase gel series assays relates to the fact that under nongrowing conditions the need for anabolic resources targeted for growth and proliferation is minimized. Transcription of the genes for many of the proteins found to be degraded in this study has been shown to be down-regulated in the stationary phase (25), and the mRNAs for selected substrate candidates (MurAA, IlvB, and AroA and MetE) diminished in wild-type cells as well as clp mutant cells (data not shown).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…An obvious explanation for the high degree of protein breakdown demonstrated by our wild-type pulse-chase gel series assays relates to the fact that under nongrowing conditions the need for anabolic resources targeted for growth and proliferation is minimized. Transcription of the genes for many of the proteins found to be degraded in this study has been shown to be down-regulated in the stationary phase (25), and the mRNAs for selected substrate candidates (MurAA, IlvB, and AroA and MetE) diminished in wild-type cells as well as clp mutant cells (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…The major physiological role of the stringent response is to prevent the continued synthesis of proteins no longer required for nongrowing cells. Almost 1,000 genes are no longer expressed when cells enter the stationary phase induced by glucose starvation, most of them being under negative stringent control (6,13,25). The issue arises of whether proteins that are no longer required and that are available in excess in nongrowing cells are stable.…”
mentioning
confidence: 99%
“…In particular, genes involved in translation and amino acid biosynthesis are targets of a negative stringent control (1,4,12,14,26,34). Consistent with the decreased growth rate of the menD mutant grown in TSB medium, a lower translational capacity was observed for the mutant, as indicated by a reduced transcriptional activity of genes encoding ribosomal proteins, aminoacyl tRNA synthetases, and translational factors.…”
Section: Vol 190 2008 Gene Expression In An S Aureus Mend Mutant 6357mentioning
confidence: 71%
“…Out of these operons, lcfA-fadRB-etfBA, lcfB, and fadNAE were found to be induced upon glucose starvation after glucose was exhausted from minimal medium by means of a DNA macroarray experiment (13), which was consistent with the DNA microarray results for glucose repression in the cells logarithmically grown in nutrient sporulation medium, except for in the case of lcfB, whose expression was not properly detected for an unknown reason (26) (http://www.genome.ad .jp/kegg/expression). In order to confirm these genome-wide profiling results, we performed Northern analysis of glucose repression of the above five operons belonging to the FadR regulon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since B. subtilis apparently possesses the genes involved in the ␤-oxidation cycle, this cycle appears to have a dispensable function under certain physiological conditions. In fact, the lcfA-fadRB-etfBA, lcfB, and fadNAE operons have been reported to be induced upon glucose starvation (13). Furthermore, the fadNAE operon is induced at the onset of sporulation (9).…”
mentioning
confidence: 99%